CFD Modeling of Film Cooling Flow with Inclined Jets - Majid A. Almas (Journal of Advances in Applied & Computational Mathematics, 2016)
Film cooling has been widely used to control temperature of high temperature and high pressure blades. In a film cooled blade the air taken from last compressor stages is ejected through discrete holes drilled on blade surface to provide a cold layer between hot mainstream and turbine components. A comprehensive understanding of phenomena concerning the complex interaction of hot gasses with coolant flows in a vane passage plays a major role in the definition of a well performing film cooling scheme. In this study turbulent film cooling flow has been studied numerically. The computational simulation is conducted by employing the Reynolds Averaged Navier-Stokes (RANS) approach. The standard k-e model with enhanced wall treatment has been implemented for modeling the turbulent flow. Effects of different cooling holes temperature have been studied on the surface of the blade and as results show the temperature of the surface reduces significantly as the temperatures of the cooling holes decreases.